2016
DOI: 10.1515/amm-2016-0205
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Thermodynamic Study of Selected in-Situ Composites from the Fe-Cr-Ni-Mo-C System

Abstract: The aim of the study was to synthesize and characterize the selected in-situ composites from the Fe-Cr-Ni-Mo-C system, additionally strengthened by intermetallic compounds. The project of the alloys was supported by thermodynamic simulations using Calculation of Phase Diagram approach via Thermo-Calc. Selected alloys were synthesized in an arc furnace in a high purity argon atmosphere using a suction casting unit. The studies involved a range of experimental techniques to characterize the alloys in the as-cast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Some published works concerning the in-situ synthesis of composite materials suggest that the experimental results should be complimented by the modelling and simulation of the solidification behaviour of the fabricated alloy system [18,19]. The use of computational thermodynamics allows an evaluation of phase stability in multicomponent systems as a function of temperature and composition and therefore provides the critical basis for understanding phase stability during the in-situ processing of composite materials [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Some published works concerning the in-situ synthesis of composite materials suggest that the experimental results should be complimented by the modelling and simulation of the solidification behaviour of the fabricated alloy system [18,19]. The use of computational thermodynamics allows an evaluation of phase stability in multicomponent systems as a function of temperature and composition and therefore provides the critical basis for understanding phase stability during the in-situ processing of composite materials [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 8(a) reveals that delta ferrite was enriched in Cr and W in comparison to the matrix, which is a consequence of strong elemental partitioning during solidification and high carbon affinity. The ferritic zones are preferential sites for the nucleation and growth of carbonitrides [22]. Moreover, EDS (Figure 8(b)) showed that both martensite and delta ferrite mainly contained Fe, Cr and W.
Figure 8 EPMA and EDS analyses of alloying elements distributions in the microstructure after standard heat treatment; (a) SEI image and element (Cr and W) mapping and (b) EDS spectrum of delta ferrite and martensite.
…”
Section: Resultsmentioning
confidence: 99%
“…Figure 8(a) reveals that delta ferrite was enriched in Cr and W in comparison to the matrix, which is a consequence of strong elemental partitioning during solidification and high carbon affinity. The ferritic zones are preferential sites for the nucleation and growth of carbonitrides [22]. Moreover, EDS (Figure 8(b)) showed that both martensite and delta ferrite mainly contained Fe, Cr and W.…”
Section: Microstructure After Annealingmentioning
confidence: 97%
“…Weld metal from classic filler metal for 7CrMoVTiB10-10 steel, 10CrMo9-10 steel and nickel base filler metals were investigated by the dilatometry. Interpretation of dilatometric diagrams can assist studies of CCT diagrams [22][23][24][25], CHT diagrams [26][27] and CTE (coefficient of thermal expansion) [28]. In this investigation coefficients of thermal expansion of P 24-IG (designated to 7CrMoVTiB10-10 steel), CMS-IG (designated to 10CrMo9-10 steel) and EPRI P87 weld metals were investigated.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%